Interpretasi Makna Hidayah Dalam al-Quran (Telaah Pemikiran Al-Rāgib al-Aṣfahānī) - Wali Ramadhani (Diya Al-Afkar: Jurnal Studi al-Quran dan al-Hadis, 2022)
This article explains the meaning of hidayah in the Qur’an from the perspective of al-Rāgib al-Aṣfahānī. Verses about hidayah are presented in the Qur'an in various ways. In some places, they seem contradictory. Through of descriptive-analytical, the author tries to explain about hidayah in the Qur’an from al-Rāgib's presentation recorded in his magnum-opus Mufradāt alfaẓ al-Qurān. He was one of the commentators in the 5th century H. The verses about hidayah described in the Qur’an are classified by al-Rāgib into four stages; the first stage is hidayah obtained by all living things on this earth (garizah, natural nature and thinking power), the second stage is hidayah given to humans in the form of preaching from the prophets and apostles, the third stage is hidayah given special by Allah to those who ask and want guidance (taufiq), the fourth stage is hidayah obtained by humans in the hereafter, namely the guidance of Allah in the beauty and pleasures of heaven.